Subnational public expenditures, short-term household-level welfare, and economic flexibility: Evidence from Nigeria - Takeshima, Hiroyuki; Balana, Bedru; Smart, Jenny; Edeh, Hyacinth O.; Oyeyemi, Motunrayo; Andam, Kwaw S. (Wiley, 2022)
Public expenditures (PEs) are critical for key public-sector functions that contribute to the development and welfare improvements. PE for agriculture, as well as social-sector PE, such as health, education, and social welfare, have been considered instrumental for income growth, poverty reduction, investment, nutritional outcomes, and resilience. However, direct evidence in developing countries like Nigeria has been relatively limited. We fill this knowledge gap by estimating the effects of subnational PE shares for agriculture, health, education, and social welfare, as well as PE size, on household-level outcomes, using nationally representative panel household data and district––as well as state-level PE data in Nigeria, and a production-function-based indicator of “flexibility.” We find that greater PE shares for agriculture, health, and social welfare, conditional on PE size, have positive effects on consumption, poverty reduction, and nonfarm business. A greater PE share for agriculture, unlike the PE shares for health or social welfare, also enhances household dietary diversity and economic flexibility between farming and nonfarm activities, an indicator of economic resilience. These effects appear to materialize through the positive impacts on agriculture. Such multidimensional benefits of greater PE for agriculture are worth attention in countries like Nigeria, which tends to allocate a lower PE share for agriculture compared to other comparable countries in Africa and elsewhere.